Nilai Feminimisme dalam Film Sundel Bolong - Nurhayati, Eni; Ahmadi, Anas; Pairin, Udjang; Yohanes, Budinuryanta (Universitas Muhammadiyah Surabaya, 2025)
The movie “Sundel Bolong” highlights the struggle of women in a patriarchal society through the character of Alisa, who faces moral and social dilemmas after becoming pregnant out of wedlock. Her transformation into Sundel Bolong illustrates an attempt to achieve existential freedom, despite having to pay with stigma and ostracization. This article uses a qualitative approach to analyze the value of feminism in the film, highlighting how women are portrayed as victims of the patriarchal system through experiences of sexual violence and betrayal. The film not only presents a horror story, but also offers insight into women's struggle against oppression, highlighting the duality of women as “angels” and “monsters” and criticizing traditional gender roles. Sundel Bolong's retaliation against her abuser becomes a symbol of resistance to patriarchy, while the theme of women's loss of existential freedom is central to the narrative.